Kern's Six Steps to implement simulation in public health crisis - Krouss, Mona; Musser, Lara; Bentley, Suzanne; Alaiev, Daniel; Uppal, Amit; Langston, Matthew D.; Arbo, John E.; Iavicoli, Laura; Lee, Alex-Sungbae; Pohlman, Jessica; Walker, Katie; Taubman, Cara; et al. (Frontiers in Disaster and Emergency Medicine, 2025)
The coronavirus disease 2019 (COVID-19) pandemic resulted in a rapid influx of critically ill patients, necessitating adding intensive care unit (ICU) beds and redeploying non-ICU clinicians to critical care areas. New York City Health + Hospitals (NYC H+H) applied the Kern's Six Steps Curriculum Design framework to deploy a ventilator simulation course across the system to build preparedness for ventilator management in non-ICU providers. In this article we describe how our quality improvement initiative prepared the largest public hospital system in the country to take care of intubated COVID patients for the “second wave” by applying Kern's Six Steps. Through this description, we offer how applying a framework, like Kern's Six Steps, is a model that structures interventions for success and can be applied to future disaster preparedness educational strategies.